Organizational readiness and implementation of colorectal cancer screening evidence-based interventions in federally qualified health centers: A cross-sectional study - Emanuelle M. Dias; Timothy J. Walker; Bijal A. Balasubramanian; Paula M. Cuccaro; Lauren Workman; Abraham Wandersman; Maria E. Fernandez (Journal of Clinical and Translational Science)
Abstract